EXAMINING SPEECH ACTS IN ENGLISH TEXTBOOKS: SIGNIFICANCE AND IMPLICATIONS FOR EFL INSTRUCTION - widiatmoko, Paulus (English Education Study Program STKIP PGRI Pacitan, 2025)
Pragmatic competence is a crucial component of cultural understanding, encompassing the ability to select and interpret expressions and utterances in specific context of communication. This aspect of language instruction often receives insufficient attention due to teacher priority on language forms over its functions. The primary objective of this study was to identify types of speech acts in the dialogues of the first and fourth editions of the